Case report: Carnivore–ketogenic diet for the treatment of inflammatory bowel disease: a case series of 10 patients - Norwitz, Nicholas G.; Soto-Mota, Adrian (Frontiers in Nutrition, 2024)
Background: Very low carbohydrate diets, including ketogenic and carnivore diets, are gaining popularity for the experimental treatment of a wide range of disorders, including inflammatory bowel disease (IBD). Methods: Participants were recruited from a social media survey. Final inclusion required a histologically confirmed diagnosis of ulcerative colitis or Crohn’s disease that was responsive to treatment with a ketogenic or carnivore diet without medication or with successful medication cessation on the diet. Clinical improvement was measured retrospectively with the Inflammatory Bowel Disease Questionnaire (IBDQ). Results: We report on 10 cases of IBD responsive to ketogenic, mostly carnivore, diets. Clinical presentations were diverse, including cases of 6 ulcerative colitis and of 4 Crohn’s disease. Clinical improvemenst were universal, with clinical improvement scores ranging between 72 and 165 points in the IBDQ. Patients’ diets comprised mostly meat, eggs and animal fats. Patients report their diets are pleasurable, sustainable, and unequivocally enhance their quality of life. Conclusions: Ketogenic and carnivore diets hold promise for the treatment of IBD, including ulcerative colitis of Crohn’s disease. These cases are consistent with preclinical and clinical literature showing an inverse association between intestinal ketone levels and IBD activity, and therapeutic effects of low residue elimination diets on colonic microbiota metabolism.